CORRELATION BETWEEN PENIS LENGTH AND ANTHOPOMETRY OF 5 YEAR OLD CHILDREN - Kurnia Indrawan, Doddy; Suryawan, Bikin; Sidiartha, Lanang; *, Arimbawa (Medicina, 2013)
Short penis still a problem for parents. Penis lenght is associated with  weight and considered abnormal in obese children. The purpose of this study was to find out the correlation between penis length and the anthropometry children aged 5 years. A cross sectional study was conducted, at the Division of Endocrinology, Department of Child Health, Medical Faculty of Udayana University, Sanglah Hospital Denpasar, during October 2010, at TK Sayang Ibu Sanglah Hospital. The calculation of the sample with a correlation coefficient of weight and  height obtained  9 people, taking in consecutive sampling and analyzed  with Pearson’s correlation. The mean body weight was 23.6 (SD 7.70) kg;  mean child height was 108.4 (SD 5.3) cm, and 47.1% were obese. The mean length of the penis was 4.7(SD1.30) cm. The correlation between weight and penis lenght was strong negative (r = -0.876; P = 0.000) and between penis length and height was r = -0.597; P = 0,011.There was a strong negative correlation between body weight and penis length and also negative correlation between penis length and height in kindergarten children. (MEDICINA 2012;43:19-22).
Keywords: penis length, weight, height, correlation